The women's knowledge about the urinary incontinence and ways of controlling the illness - Derewiecki, Tomasz; Duda, Marta; Majcher, Piotr; Mroczek, Krzysztof (Polish Journal of Public Health, 2012)
Introduction. The urinary incontinence (UI) is considered one of the most often occurring chronic diseases in wo-men. It consists in uncontrolled leakage of urine through the urethra. It concerns 17-60% of the female population.Aim. The main aim of the present work was to investigate women’s knowledge about the problem of urinary incontinence and its practical application dealing with the problem, what would contribute to improving the quality of life.Material and methods. There were 101 female patients surveyed from the Zamość Rehabilitation Center of University of Management and Administration. The population was diversified with regard to age, place of living and education. The age of the examined women varied from 30 to 87 years. The research tool used was an author`s questionnaire survey. In the statistical analysis of the results Microsoft Excel program was applied. The significance level was accepted for p